Dry aging: an old process revisited - Campbell, R.E.; Hunt, Melvin C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Dry aging of beef cuts, once considered the "gold standard" for premium palatability, is practiced by only a few processors. We were asked by a major southern meat purveyor to study variables of dry-aging processing. Detailed sensory analyses of flavor, juiciness, and tenderness clearly indicated that beef loins dry aged for 14 and 21 days were superior for all three traits to a product vacuum aged for 14 days and to a product dry aged for 7 days. In addition, dry- aged steaks could be vacuum packaged and stored for up to 16 days without losses in palatability. Dry aging definitely intensified desirable flavor traits and reduced flavor notes typical of vacuum aging. Counts showed that dry aging controlled bacteria. Dry aging, properly done, produces beef steaks with desired eating characteristics for the high-end, value-added markets.
Keywords: Beef; Dry aging; Meat sensory attributes; Meat physical attributes; Microbiology